PENDEKATAN DALAM PENDIDIKAN ISLAM - Delisa Delisa; Eli Ernawati Eli Ernawati; Arnadi Arnadi (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The progress of a country is very dependent on the progress of its education (including Islamic education), and education is closely related to the use of approaches and methods used during the teaching and learning process. Approaches and methods should be mastered by a teacher in order to achieve the goals that have been set. The use of approaches and methods that are appropriate and appropriate to the subject matter as well as the existing situation and conditions will lead students to mastery of the expected lesson content. The importance of approaches and methods in education is so important that educators are required to be professional in developing these approaches and methods. Educators must know the advantages and disadvantages of each approach and method that will be used and determine the most appropriate choice so that students are more active and critical in the learning process. And the most important thing is that with this approach and method, students reach their desired goals.